2013
DOI: 10.1056/nejmsa1204720
|View full text |Cite
|
Sign up to set email alerts
|

Simulation-Based Trial of Surgical-Crisis Checklists

Abstract: In a high-fidelity simulation study, checklist use was associated with significant improvement in the management of operating-room crises. These findings suggest that checklists for use during operating-room crises have the potential to improve surgical care. (Funded by the Agency for Healthcare Research and Quality.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
246
0
13

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 491 publications
(265 citation statements)
references
References 29 publications
6
246
0
13
Order By: Relevance
“…For instance, Neily et al 3 found that surgical team training which incorporated surgical checklists along with communication strategies was associated with a significant reduction in surgical mortality. Arriaga et al 4 found that checklists dramatically improved adherence to critical processes of care in simulated scenarios of surgical crises. Studies have suggested that checklists may reduce errors for many reasons, including ensuring that all critical tasks are carried out, encouraging a non-hierarchical team-based approach, enhancing communication, catching near misses early, anticipating potential complications, and having technologies to manage anticipated and unanticipated complications.…”
Section: Strategies For Patient Safetymentioning
confidence: 99%
“…For instance, Neily et al 3 found that surgical team training which incorporated surgical checklists along with communication strategies was associated with a significant reduction in surgical mortality. Arriaga et al 4 found that checklists dramatically improved adherence to critical processes of care in simulated scenarios of surgical crises. Studies have suggested that checklists may reduce errors for many reasons, including ensuring that all critical tasks are carried out, encouraging a non-hierarchical team-based approach, enhancing communication, catching near misses early, anticipating potential complications, and having technologies to manage anticipated and unanticipated complications.…”
Section: Strategies For Patient Safetymentioning
confidence: 99%
“…The latter were distributed to all wards and to all operation rooms [28]. For example, the recommendations regarding the screening and therapy of preoperative anemia in Frankfurt were integrated into flow charts and are displayed in the surgical ambulances identifying target patient groups.…”
Section: Patient Blood Managementmentioning
confidence: 99%
“…Encourage trainees to make use of checking routines during acute crises. Even in the most dire of situationswhen a patient has arrested -using pre-printed checklists improves timely administration of life saving treatment (Arriaga et al 2013). …”
Section: Tipmentioning
confidence: 99%
“…By adopting a systematic framework, the extraneous load of checking can be reduced, allowing trainees to focus on finding mistakes. Often, these frameworks are organized into checklists, which have helped physicians reduce error in a variety of contexts (Wolff et al 2004;Haynes et al 2009;Winters et al 2009;Ely et al 2011;Arriaga et al 2013;Sibbald et al 2013).…”
Section: Tipmentioning
confidence: 99%